The association between hypertensive angiopathy and cerebral amyloid angiopathy in primary intracerebral hemorrhage - Zhu, Yuyi; Liu, Lu; Zhong, Luyao; Cheng, Yajun; Zhang, Shihong; Wu, Bo; Wang, Deren; Xu, Mangmang (Frontiers in Neurology, 2023)
Objective To determine the association between the burden of cerebral small vessel disease (CSVD) due to hypertensive angiopathy (HA) and cerebral amyloid angiopathy (CAA) on MRI in patients with primary intracerebral hemorrhage (ICH). Methods Patients with primary ICH admitted to our center from March 2012 to November 2021 were consecutively enrolled. We used multivariate binary and ordinal regression analyses to assess the association between HA-CSVD burden and CAA-CSVD burden. Lobar cerebral microbleeds (CMBs) were categorized into three level of severity: 0–1, 2–4, and ≥ 5 lobar CMBs. A high CAA-CSVD score was defined as a CAA-CSVD score of ≥3. Results Overall, 222 participants (mean age 59.88 ± 13.56) were included into analysis. Age and ICH etiology differed among different lobar CMB severity and between the presence and absence of high CAA-CSVD score (all p < 0.05). Positive associations between HA-related markers and both lobar CMB severity and high CAA-CSVD score (p < 0.05 for the presence of lacune, deep CMBs ≥5, the presence of WMH, and HA-CSVD score) were observed in univariate analysis. These associations remained significant after adjusting for age, sex, ICH etiology, and potential vascular risk factors. The distribution of CAA-CSVD score was significantly different between patients with and without CMBs ≥5 (adjusted OR 2.351, 95% CI 1.242–4.455, p = 0.009) after correcting for age, sex, ICH etiology, and vascular risk factors. Conclusion Our study provides evidence of an association between HA-CSVD and CAA-CSVD in patients with primary ICH, which needs to be verified in future studies.